PERANCANGAN SISTEM INFORMASI AKADEMIK DAN KEMAHASISWAAN BERBASIS WEB (STUDI KASUS: LLDIKTI WILAYAH V) - Yoko Khomarudin Habiburochman; Deden Hardan Gutama; Andri Pramuntadi; Dita Danianti (Jurnal Informatika Teknologi dan Sains (Jinteks), 2025)
LLDIKTI Region V is responsible for facilitating higher education implementation in Yogyakarta region, but currently lacks a specific platform to display academic and student affairs data to the public. SINTA, research, community service, KIP Kuliah, RPL, PKM, MBKM, and student achievement data are stored in separate internal platforms accessible only to certain administrators. This research aims to design and develop a web-based academic and student information system named "SADEWA" using waterfall method for LLDIKTI Region V. The development method uses Laravel 11 framework, MySQL database, Model-View-Controller architecture, and ApexCharts data visualization. The system successfully displays data from 100 universities with a total of 3,375 data entries including research (125 entries), community service (75 entries), KIP Kuliah (256 entries), RPL (419 entries), PKM (79 entries), student achievements (2,255 entries), and university clustering (166 entries). SADEWA provides public access for Guest users and management access for Admin/Super Admin with bar chart and pie chart visualization features and data download capabilities in PNG, SVG, and CSV formats. System testing using black box testing method with 31 scenarios shows 100% results according to predetermined specifications.